2016
DOI: 10.1039/c5ra26056f
|View full text |Cite
|
Sign up to set email alerts
|

Influence of silica nanoparticles on mass transfer in a membrane-based micro-contactor

Abstract: Experiments were performed in a membrane based micro-contactor The results showed that nanoparticles are more effective on mass transfer at lower flow rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…(inverse Debye length) (12) where, ε 0 is the permittivity of free-space, ε r is the relative permittivity of the medium, η is the viscosity of the medium, k is the Boltzmann constant, T is the temperature, Z is the valency of the ions of the assumed symmetric electrolyte-i.e., equal for positive and negative ions Z = Z + = −Z − , e is the elementary positive charge, ζ is the zeta-potential at the particle surface, D + and D − are the diffusion coefficients of the positive and negative ions respectively, N A is the Avogadro number, and C ∞ is the concentration (in mM) of the solute far from the particle surface. n is the number of species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(inverse Debye length) (12) where, ε 0 is the permittivity of free-space, ε r is the relative permittivity of the medium, η is the viscosity of the medium, k is the Boltzmann constant, T is the temperature, Z is the valency of the ions of the assumed symmetric electrolyte-i.e., equal for positive and negative ions Z = Z + = −Z − , e is the elementary positive charge, ζ is the zeta-potential at the particle surface, D + and D − are the diffusion coefficients of the positive and negative ions respectively, N A is the Avogadro number, and C ∞ is the concentration (in mM) of the solute far from the particle surface. n is the number of species.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of a small fraction of nanoparticles as a suspension in a fluid (also referred to as nanofluids) seems to immensely influence various phenomenon like diffusion [1][2][3], absorption [4][5][6][7][8][9], extraction [10][11][12], in radiation [13], electric conductivity [14], evaporation [15] and reaction kinetics of chemical processes. Mass transfer studies in dye-diffusion by Krishnamurthy et al 1 and others [2,3] have demonstrated, through dramatic visual effects, that the presence of nanoparticles increases the effective diffusivity up to 14 folds.…”
Section: Introductionmentioning
confidence: 99%
“…Rahbar Kelishami et al [152] In another study, Ashrafmansouri et al [154] used a membrane based micro-contactor to perform an experimental study of the improvement of mass transfer in the contactor using SiO 2 nanoparticles. The enhancement caused by the nanoparticles was more pronounced at lower flow rates.…”
Section: Saien and Zardoshtimentioning
confidence: 99%
“…According to their results, the enhancement was due to the Brownian motion of the nanoparticles motion and the induced microconvection. In contrast, the decrease in mass transfer above 0.001 vol.% was attributed to the reduction in the free volume and nanoparticle aggregation at greater concentrations [154]. The experimental studies of the effect of nanoparticles on the mass transfer performance of liquid-liquid extraction contactors in the absence of a magnetic field are summarized in Table 3.…”
Section: Saien and Zardoshtimentioning
confidence: 99%
“…Mass‐transfer phenomenon in two‐phase MCs and MRs has been studied in the literature . Some researchers have investigated mass transfer in the liquid‐liquid slug flow using different sizes of capillaries .…”
Section: Introductionmentioning
confidence: 99%